2015
DOI: 10.28945/2209
|View full text |Cite
|
Sign up to set email alerts
|

Using Technology in Gifted and Talented Education Classrooms: The Teachers’ Perspective

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 94 publications
(264 reference statements)
0
6
0
1
Order By: Relevance
“…This body of knowledge is not new to pandemic times. Much of the existing work has recognised strengths; it frequently applies multidisciplinary perspectives, multiple methods, and a crossnational perspective which we would expect to take up in lockdown times (Kong and Song, 2014;Zimlich, 2015;Bhakta and Dutta, 2016). Some studies draw attention to the role of the government, social norms, and future directions (Buckenmeyer, 2010;DeCoito and Richardson, 2018;Raja and Nagasubramani, 2018).…”
Section: Current Research On the Impact Of New Technologies On Learningmentioning
confidence: 99%
“…This body of knowledge is not new to pandemic times. Much of the existing work has recognised strengths; it frequently applies multidisciplinary perspectives, multiple methods, and a crossnational perspective which we would expect to take up in lockdown times (Kong and Song, 2014;Zimlich, 2015;Bhakta and Dutta, 2016). Some studies draw attention to the role of the government, social norms, and future directions (Buckenmeyer, 2010;DeCoito and Richardson, 2018;Raja and Nagasubramani, 2018).…”
Section: Current Research On the Impact Of New Technologies On Learningmentioning
confidence: 99%
“…Similarly, Martin et al (2010) state that effective educational technologies depend on professional development programs and ongoing support. Zimlich (2012) declares that exposure to more experienced people in terms of technology will increase the success of other teachers when it comes to using technology, thanks to local support structures such as mentorship. It has been shown that ensuring the time, proximity, responsiveness, and availability of support structures makes a difference for teachers.…”
Section: Discussionmentioning
confidence: 99%
“…The technology-based classroom has come to help remove the ineffective and outdated methods of teaching and techniques by giving teachers the chance to plan a curriculum according to the differentiation instruction (Mulrine, 2007). In terms of its use in the classroom, not all technology upholds the purpose of the curriculum, but teachers maneuver to introduce technology into their classroom to help support teaching and learning (Zimlich, 2015). A digital tool such as Google Docs provides a scholar with a chance to work on a writing task collaboratively with their colleagues in distant locations (Eckstein, 2009).…”
Section: Integrating Technology Into the Classroommentioning
confidence: 99%